Identification and Characterization of the OCT4 Upstream Regulatory Region in Sus scrofa - Seung-Hun Kim; Kwang-Hwan Choi; Dong-Kyung Lee; Mingyun Lee; Jae Yeon Hwang; Chang-Kyu Lee (Stem Cells International)
OCT4 plays pivotal roles in maintaining pluripotency during early mammalian embryonic development and in embryonic stem cells. It is essential to establish a reporter system based on the OCT4 promoter region to study pluripotency. However, there is still a lack of information about the porcine OCT4 upstream reporter system. To improve our understanding of the porcine OCT4 regulatory region, we identified conserved regions in the porcine OCT4 promoter upstream region by sequence-based comparative analysis using various mammalian genome sequences. The similarity of nucleotide sequences in the 5′ upstream region was low among mammalian species. However, the OCT4 promoter and four regulatory regions, including distal and proximal enhancer elements, had high similarity. Next, a functional analysis of the porcine OCT4 promoter region was conducted. Luciferase reporter assay results indicated that the porcine OCT4 distal enhancer and proximal enhancer were highly activated in mouse embryonic stem cells and embryonic carcinoma cells, respectively. A comparison analysis of naïve and primed state marker gene expression in a dual-reporter assay showed that the expression levels of naïve and primed markers differed in fluorescence signal between high-expressing cells and low-expressing cells. Similar to OCT4 upstream-based reporter systems derived from other species, the porcine OCT4 upstream region-based reporter constructs showed exclusive expression patterns depending on the state of pluripotency. This work provides basic information about the porcine OCT4 upstream region and various porcine OCT4 fluorescence reporter constructs, which can be applied to study species-specific pluripotency in early embryo development and the establishment of embryonic stem cells in pigs.